Study the Impact of Corrosive Pollutants on Building Materials Corrosion - Rajesh Kumar Singh; Pankaj Kumar Singh; Deepmala Kumari (International Journal of Fracture Mechanics and Damage Science, 2025)
Reinforced concrete structures (RCS) may be made more resistant to corrosion by using fiber reinforced polymers (FRP). One of the primary concerns with reinforced concrete constructions is corrosion. It causes disintegration in building material components by interactions with salts, acids, and alkalis. Both within and outside of reinforced properties, pollutants and effluents accelerate disbanding. When bio-waste and building materials come into contact, microorganisms and macro organisms, grow and emit acid compounds that hasten the corrosive process. Deformation of building block components is also caused by hostile agents such as acid rain, global warming, greenhouse gases, heat waves, climatic change, humidity, and moisture. Iron bars in reinforced concrete can corrode due to the prevalence of chloride ions in sea conditions. As the temperature of the atmosphere rises, the corrosion of building materials increase. Particulates make building materials particularly susceptible to corrosion. Chemical, biological, and electrical responses occur as a result of corrosive chemicals attacking the interface of reinforced frameworks and some of them entering through osmosis or diffusion methods. Such ambient conditions cause rebar steel to corrode in a range of ways, including galvanic, pitting, crevice, stress, intergranular, blistering, brittleness, erosion, and cavitations. It causes the concrete and rebar steel to collapse. Certain gases cause swelling and dissolving corrosion on the surface of concrete buildings by absorption moisture. The physical, chemical, and mechanical aspects of building block components are changed by corrosion techniques, which also detract from face features. Corrosion-resistant concrete is preserved by fiber-reinforced polymers. Developed countries spend 4% of their gross national product on corrosion preventative measures, part replacement, and upkeep. Mining, thermal power plants, refineries for oil and gas burning fossil fuels, chemical wastes, biological wastes, garbage from people, household wastes, agricultural wastes, animal wastes, food grain wastes, hospital trash, chimney flue gases, and industrial effluents are the main sources of corrosive substances. As effluents, these causes emit acids, alkalis, salts, organic compounds, metals, carbon oxides, nitrogen oxides, sulfur oxides, halogen oxides, sulfur hydride, nitrogen hydride, volatile organic molecules as flue gases, and other contaminants. Water, air, and soil are all contaminated by these toxic substances. Sand, stones, cements, iron bars, bricks, and water are the basic elements required for R C structures. The corrosive compounds specified above create an unfavorable environment for construction materials. This corrosive impact shortens the life of RC structures and causes internal as well as external disintegration, raising doubts about their stability, the lifespan, and durability. RC structures may be protected from corrosion using a variety of technologies. However, these methods did not provide them with sufficient safeguards. Therefore, fiber-reinforced polymers will be used as this effort to reduce RC structure corrosion.
Keywords: Acid rain; Building materials; Effluents; Flues gases; Pollutants; R C structures and Fiber Reinforced Polymers; Weather; wastes